The Effect of Anxiety and Burnout on The Motivation of Nurses' Work in The Era of The Covid-19 Pandemic at The Regional General Hospital in D.I. Yogyakarta Province - Baharuddin, M Akhyar; Rosa, Elsye Maria (Universitas Aisyah Pringsewu, 2022)
Health workers, who have been at the forefront of the fight against COVID-19, have been working hard to treat COVID-19 positive patients. Several of these medical staff became infected with COVID-19. This study aims to analyze the impact of anxiety and burnout on nurses' work motivation at a public hospital in Yogyakarta. The population of this study is all nurses who provide services to Covid-19 patients, with 167 nurses being sampled using total sampling, data analysis using The structural equation modelling model. The study showed that anxiety had a positive and significant effect on nurses' burnout, with an original sample value (O) of 0.175, an at-statistical value of 2,332, and a p-value of 0.020. The effect of anxiety on work motivation was affected by the value (O) of -0.275, the t-statistical value of 3,883, and the p-value of 0.000, indicating that anxiety had a negative and significant effect on the work motivation of nurses', and the effect of burnout on motivation was affected by the value (O) of -0.199, the t-statistical value of 2,296, and the p-value of 0.000, indicating that burnout was effected so there is an impact of anxiety and burnout on nurses' work motivation at a public hospital in Yogyakarta. Abstrak: Tenaga kesehatan sebagai garda terdepan dalam melawan COVID-19 telah berusaha keras untuk mengobati pasien yang positif COVID-19. Tidak sedikit dari tenaga medis tersebut yang ikut tertular COVID-19 bahkan sampai meninggal dunia. penelitian ini bertujauan meneliti pengaruh kecemasan dan burnout terhadap motivasi kerja perawat pada era pandemic Covid-19 di RSUD di Yogyakarta.Jenis penelitian merupakan kuantitatif dengan metode cross-sectional. Populasi penelitian ini adalah seluruh perawat yang memberikan pelayanan bagi pasien Covid-19 di RSUD di Yogyakarta dengan teknik sampling total sampling, jumlah sampel sebanyak 167 perawat. Teknik analisis data dalam penelitian ini menggunakan model Structural Equation Modeling.Hasil analisis didapatkan nilai original sample (O) sebesar 0,175, nilai t-statistik sebesar 2,332, p-value 0,020, maka kecemasan berpengaruh positif dan signifikan terhadap burnout petugas medis. Kemudian pengaruh kecemasan terhadap motivasi didaptkan nilai (O) sebesar -0,275, nilai t-statistik sebesar 3,883, p-value 0,000, maka kecemasan berpengaruh negatif dan signifikan terhadap motivasi kerja petugas medis, dan pengaruh burnout terhadap motivasi didapatkan nilai (O) sebesar -0,199, nilai t-statistik sebesar 2,296, p-value 0,000, maka burnout berpengaruh negatif dan signifikan terhadap motivasi kerja petugas medis. Sehingga dapat disimpulkan terdapat pengaruh kecemasan dan burnot pada motivasi kerja perawat di RSUD di Yogyakarta.